Question
upstudy study bank question image url

2) Consider the function \( f(x)=2 x^{2} \) and \( p(x)=\left(\frac{1}{2}\right)^{x} \). a) Restrict the domain of \( f \) so that the inverse of \( f \) will also be a function. b) Write down the equation of the inverse of \( p \) in the form \( p^{-1}(x)=\ldots \) c) If the inverse of another function is \( g^{-1}(x)=2 x-4 \). Determine the equation of \( g(x) \).

Ask by Gray Ortega. in South Africa
Feb 20,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

a) Restrict the domain of \( f(x) = 2x^2 \) to \( x \geq 0 \). b) The inverse of \( p(x) = \left(\frac{1}{2}\right)^x \) is \( p^{-1}(x) = \log_{\frac{1}{2}}(x) \). c) If \( g^{-1}(x) = 2x - 4 \), then \( g(x) = \frac{x + 4}{2} \).

Solution

We are given the functions f(x) = 2x² and p(x) = (1/2)ˣ. We wish to: a) Restrict the domain of f so its inverse is a function. b) Find the inverse of p in the form p⁻¹(x) = … c) Given g⁻¹(x) = 2x – 4, find g(x). Let’s work through each part step by step. ──────────────────────── Part (a) For a function to have an inverse that is also a function, the function must be one-to-one (injective). The function f(x) = 2x² is not one-to-one over the real numbers because, for example, f(2) = 8 and f(–2) = 8. A common remedy is to restrict the domain so that the function is either only increasing or only decreasing. A common restriction is to choose x ≥ 0, which gives a monotonically increasing function. Thus, by restricting the domain to [0, ∞), f becomes one-to-one and its inverse is defined. ──────────────────────── Part (b) We wish to find the inverse of p(x) = (1/2)ˣ. The steps are: 1. Begin with y = (1/2)ˣ. 2. In order to solve for x, take the logarithm base (1/2) on both sides:   x = log₍₁/₂₎(y). Since we want the inverse function written as p⁻¹(x), we interchange x and y:   p⁻¹(x) = log₍₁/₂₎(x). Thus, the inverse is:   p⁻¹(x) = log₍₁/₂₎(x). ──────────────────────── Part (c) We are given that g⁻¹(x) = 2x – 4 and need to find the corresponding function g(x). Recall that g and g⁻¹ are inverses, so:   g(g⁻¹(x)) = x. However, a more straightforward way is to “invert” the function g⁻¹(x). Write   y = 2x – 4 and solve for x in terms of y. Step 1. Start with:   y = 2x – 4 Step 2. Add 4 to both sides:   y + 4 = 2x Step 3. Divide both sides by 2:   x = (y + 4)/2 Now, reinterpret this equation. Since we began with y = g⁻¹(x) and ended with x in terms of y, the inverse of g⁻¹ is the function g. Renaming y back as the variable x, we get:   g(x) = (x + 4)/2. ──────────────────────── Final Answers: a) Restrict the domain of f to x ≥ 0. b) p⁻¹(x) = log₍₁/₂₎(x). c) g(x) = (x + 4)/2.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Beyond the Answer

To ensure \( f(x) = 2x^2 \) has an inverse that is also a function, we should restrict its domain to either \( x \geq 0 \) or \( x \leq 0 \). For instance, choosing \( x \geq 0 \) makes \( f \) a one-to-one function, allowing us to find a clean inverse without ambiguity in y-values. For the function \( p(x) = \left(\frac{1}{2}\right)^{x} \), we can find the inverse by solving for \( x \) in terms of \( y \). Setting \( y = p(x) \) gives \( y = \left(\frac{1}{2}\right)^{x} \). Taking the logarithm, we find \( x = -\log_{1/2}(y) \), giving us the inverse as \( p^{-1}(x) = -\log_{1/2}(x) \).

Related Questions

Latest Pre Calculus Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy